The impact of state aid on the survival and financial viability of aided firms - Sven Heim; Kai Hüschelrath; Philipp Schmidt-Dengler; Maurizio Strazzeri (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
We estimate the causal impact of restructuring aid granted by the European Commission between 2003 and 2012 on the survival and financial viability of aided firms. Using a comprehensive dataset we find that restructuring aid increases a firm's average survival time by 8 to 15 years and decreases the hazard rate by 58 to 68 percent, depending on the definition of firm survival. Further analysis finds strong support that, in the longer run, aid receiving firms have a significantly higher probability to improve their financial viability than the counterfactual group.
urn:nbn:de:bsz:180-madoc-409967
Keywords: C41; D62; D73; G33; G38; H23; L52; L98; O52; 330; government policy; state aid; ex-post evaluation; survival; European Union